Hidden aftershocks: an assessment of the mental health and psychosocial status and needs of earthquake-affected communities in Rasuwa, Nuwakot, and Makwanpur district. (2017)
SUMMARY: This report presents the results of an assessment of the psychosocial and mental health status and needs of communities in Rasuwa, Nuwakot, and Makwanpur districts of Nepal. The assessment took place between November 2016 and January 2017, approximately 18 months after the 2015 Nepal earthquake, and was conducted by Transcultural Psychosocial Organization Nepal (TPO Nepal) with support from the Nepal Delegation of the American Red Cross, the Nepal Red Cross Society, and other Red Cross consortium partners. The aim of this assessment was to evaluate the long-term psychosocial and mental health needs of the affected population in order to develop appropriate interventions to address those needs. This assessment used a mixed method approach including both quantitative and qualitative techniques. The assessment comprised of 510 household surveys, 30 key informant interviews, and 12 focus group discussions. The assessment followed Inter-Agency Standing Committee (IASC Nepali version) guidelines, as well as good practice principles for assessments outlined by the World Health Organization and the United Nations High Commissioner for Refugees (WHO/UNHCR, 2012). Key Findings Key quantitative findings • Most respondents (73.2%) from earthquakeaffected communities reported income/ livelihood as their most pressing need, followed by shelter (63.5%), and support to cope with distress/tension (61.0%). • The most commonly reported mental health and psychosocial problems were depression symptoms (39.4%), anxiety symptoms (38.4%), alcohol use problems (25.5%), and suicidal thoughts (21.7%). • Reports of post-traumatic stress symptoms were relatively lower (16.3%) than other mental health problems. • Symptom of mental health problems were relatively higher among women, individuals who were widowed, separated or divorced from their partners, and members of minority ethnic groups including Chepang, Magar, Newar, and Tharu. • Members of households that had previously been identified by the Red Cross program as "most vulnerable" reported higher rates of mental health and psychosocial problems. Key qualitative findings • Fear, worry, insomnia, fainting attacks, anxiety, depression, and suicidal thoughts were common mental health and psychosocial problems reported in all assessment districts. • Children, women, and the elderly were more at risk of having mental health and psychosocial problems. • Gathering together in public places, participating in cooperatives, helping one another, religious group practices, engaging in agricultural work, listening to music, watching TV, practicing yoga, reading books, and talking about problems with trusted friends and family were common positive coping mechanisms. • However, more negative coping strategies such as gambling and smoking cigarettes were present, and alcohol intake was reported to be on the rise following the earthquake. • Traditional healers and religious leaders were commonly reported informal sources of support while health posts and psychosocial counseling services provided by various organizations were the formal resources available in the communities. Recommendations • There is an urgent need for the government and other service providers (including the Red Cross) to coordinate to address the most immediate needs in earthquake affected communities; this assessment identified livelihoods, shelter, and support to cope with distress as the three most commonly reported needs. • Both specialized and non-specialized mental health services should be provided immediately for populations at high risk of mental health and psychosocial problems. These include women, older people, households previously identified by a Red Cross assessment as "most vulnerable", and the Chepang community, which is a highly marginalized ethnic group with significant populations in the Red Cross earthquake recovery program areas in Makwanpur. • Community-based service providers (including Red Cross earthquake recovery program staff and volunteers, Female Community Health Volunteers, and traditional healers) should be trained to identify symptoms of mental health problems, provide basic MHPSS services, sensitize the community to mental health problems help reduce stigma, and refer people for more advanced care when necessary. • Mental health and psychosocial support services should be integrated into Nepal's existing government health care delivery and protection system, and must be predicated on evidence-based practices and approaches such as IASC guidelines and mhGAP. Continued lobbying and advocacy around mental health and psychosocial issues is crucial at both the center and district level.